A Novel Approach to Developing Biomimetic ("Nacre‐Like") Metal‐Compliant‐Phase (Nickel–Alumina) Ceramics through Coextrusion. Issue 45 (30th September 2016) - Wilkerson, Ryan P.; Gludovatz, Bernd; Watts, Jeremy; Tomsia, Antoni P.; Hilmas, Gregory E.; Ritchie, Robert O.
Abstract : Bioinspired "brick‐and‐mortar" alumina ceramics containing a nickel compliant phase are synthesized by coextrusion of alumina and nickel oxide. Results show that these structures are coarser yet exhibit exceptional resistance‐curve behavior with a fracture toughness three or more times higher than that of alumina, consistent with significant extrinsic toughening, from crack bridging and "brick" pull‐out, in the image of natural nacre.